Raman Spectroscopy Analysis of the Structure and Surface Chemistry of Ti3C2Tx MXene - Sarycheva, Asia; Gogotsi, Yury (Chemistry of materials, 2020)
Raman spectroscopy is one of the most useful tools for the analysis of two-dimensional (2D) materials. While MXenes are a very large family of 2D transition metal carbides and nitrides, there have been just a few Raman studies of materials from this family. Here, we report on a systematic study of the most widely used and most important MXene to date: Ti3C2Tx. By synthesizing material using different methods, we show that Raman spectra of Ti3C2Tx are affected not only by the composition and surface groups but also by intercalated species and stacking. Due to a plasmonic peak of Ti3C2Tx around 785 nm, resonant conditions are achieved, enabling us to observe an extra peak at ~120 cm–1, when excited with a red diode laser. We report differences in Raman spectra collected from single flakes of Ti3C2Tx, colloidal solutions, and multilayer films. Lastly, we show how an undesirable photoluminescent background could serve as evidence of material degradation, which leads to the formation of defective titania and amorphous carbon. Overall, this study shows how Raman spectroscopy can be used for the characterization of important emerging 2D materials: MXenes.